Strategi Dinas Pariwisata Dalam Pengembangan Destinasi Wisata Pantai Pandaratan, Kecamatan Sarudik, Kabupaten Tapanuli Tengah - Ifo Siska Sigalingging; Elvri Teresia Simbolon; David Fero; Mery Silalahi; Liyus Waruwu (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This study aims to determine the strategy of the Tourism Office in developing the Pandaratan Beach tourist destination, Sarudik District, Central Tapanuli Regency. This study uses a qualitative method with a descriptive approach. Data were collected through direct field observations, in-depth interviews, and documentation of a number of informants deemed relevant, namely the Tourism Office, Pokdarwis, the community as managers, business actors, and tourists. The results show that the Tourism Office's strategy in developing Pandaratan Beach has been formulated based on the Central Tapanuli Regency Tourism Office's strategic plan (Renstra). This strategy focuses on equitable distribution of development infrastructure with a superior commodity-based approach, which aims to support tourist attractions and increase the contribution of the tourism sector to regional development. The strategy implementation is realized through various programs, including proposing basic infrastructure development, human resource development through training, destination promotion through social media, development of natural tourism products, and the formation and empowerment of tourism awareness groups (Pokdarwis) as drivers of tourism awareness campaigns. The implications of this study indicate that the development of Pandaratan Beach has not been fully optimal and still faces several obstacles, such as limited supporting facilities, less than optimal tourism services, and uneven community participation, so that the impact on the quality of tourism services, increasing community participation, and the sustainability of the destination still needs to be strengthened. Therefore, a comprehensive and sustainable strengthening of the strategy is needed through cooperation from related parties so that the Pandaratan Beach tourist destination can develop more optimally based on superior commodities.